Síndrome da fragilidade no idoso comunitário com osteoartrite Frailty syndrome in the community-dwelling elderly with osteoarthritis - Rita de Cássia Corrêa Miguel; Rosângela Corrêa Dias; João Marcos Domingues Dias; Silvia Lanziotti Azevedo da Silva; Paulo Roberto Menicucci Filho; Tatiana Moreira S. Ribeiro (Revista Brasileira de Reumatologia, 2012)
OBJETIVO: Caracterizar e comparar idosos comunitários com osteoartrite (OA) de joelhos e/ou quadris, com enfoque na síndrome da fragilidade. MéTODO: Estudo transversal com avaliação de características sociodemográficas, comorbidades, medicamentos, depressão, antropometria, quedas, dor, rigidez, função, fragilidade e avaliação subjetiva da saúde em idosos com OA de joelhos e/ou quadris a partir de subamostra do estudo sobre fragilidade em idosos brasileiros (FIBRA). RESULTADOS: A amostra final foi composta de 58 idosos (74 ± 5,50 anos), como segue: 17 (29,31%) não frágeis, 28 (48,28%) pré-frágeis e 13 (22,41%) frágeis. O número de medicamentos foi maior no grupo frágil em comparação ao não frágil (7,00 ± 2,00 e 4,00 ± 2,00, respectivamente; P = 0,001). O Índice de Massa Corporal foi menor nos idosos não frágeis em comparação aos pré-frágeis e frágeis (média de 27,00 ± 4,50 kg/m², 30,00 ± 4,00 kg/m² e 34,00 ± 8,00 kg/m², respectivamente; P = 0,018). Depressão foi mais prevalente no grupo frágil. Em relação à saúde comparada ao ano anterior, houve diferença: 64,3% dos pré-frágeis e 46,2% dos frágeis acreditavam que sua saúde piorou; entre os não frágeis, 52,9% consideraram que a saúde permaneceu igual (P = 0,016). Quanto ao nível de atividade em relação ao ano anterior, pré-frágeis e frágeis relataram que houve piora (P = 0,010). Quanto à função e à autoeficácia para quedas, os frágeis mostraram-se piores que os demais (P = 0,023 e 0,017, respectivamente). Os outros itens avaliados não apresentaram diferenças significativas entre os grupos. CONCLUSÃO: Idosos com OA e fragilidade usam maior número de medicamentos, são mais obesos e mais deprimidos, têm pior percepção da saúde e do nível de atividade em relação ao ano anterior e pior autoeficácia para quedas e para função física. OBJECTIVE: To characterize and compare community-dwelling elderly with knee and/or hip osteoarthritis (OA), focusing on the frailty syndrome. METHOD: Cross-sectional study of the elderly with knee and/or hip OA, using a subsample from the study of frailty in the Brazilian elderly (FIBRA), assessing the following: sociodemographic characteristics, comorbidity, medications, depression, anthropomorphic data, falls, pain, stiffness, physical function, and frailty. The subjective assessment of health was also performed. RESULTS: The final sample comprised 58 elderly (mean age, 74 ± 5.5 years) as follows: 17 (29.31%) non-frail, 28 (48.28%) pre-frail, and 13 (22.41%) frail. The frail elderly received more medications than the non-frail ones (7.00 ± 2.00 and 4.00 ± 2.00, respectively; P = 0.001). The mean Body Mass Index was lower in the non-frail elderly as compared with those of the pre-frail and frail ones (27.00 ± 4.50 kg/m², 30.00 ± 4.00 kg/m², and 34.00 ± 8.00 kg/m², respectively; P = 0.018). Depression was more prevalent in the frail group. Compared to the previous year, there was a difference in the health status of the groups as follows: 64.3% of the pre-frail elderly and 46.2% of the frail ones believed their health deteriorated, and 52.9% of the non-frail elderly considered that their health status remained unchanged (P = 0.016). When comparing the current physical activity levels with those of the previous year, the pre-frail and frail elderly reported a worsening (P = 0.010). Regarding physical function and fall-related self-efficacy, the frail elderly were worse than the others (P = 0.023 and 0.017, respectively). There were no significant differences between the groups for the remaining items analyzed. CONCLUSION: The elderly with OA and frailty use more medications, are more obese and depressed, have a poorer perception of their own health and of their level of activity as compared with that of the previous year, have a worse fall-related self-efficacy, and worse physical function.